Readiness of the health department in maternal and child health service programs during the COVID-19 pandemic in Bolaang Mongondow Regency - Mandagi, Chreisye K. F.; Kalesaran, Angela F. C.; Moningka, Maya E. W. (International Journal Of Community Medicine And Public Health, 2022)
Background: The current COVID-19 pandemic poses a major challenge in efforts to improve the health status of the Indonesian people and has an impact on maternal and child health services, which can be seen from the decline in K1, K4 and infant care services in Bolaang Mongondow Regency. This is due to public and staff concerns about the transmission of COVID-19. In some areas, there were even temporary closures of health service facilities, especially in posyandu and puskesmas. Methods: The research method used is qualitative through a case study at the Bolaang Mongondow district health office which was conducted through in-depth interviews using interview guidelines with 3 informants, namely the head of the health office as a key informant and 2 other informants namely the head of the family health sector and the head of the infectious disease control section then recorded. using a tape recorder. Results: The results of this study are unclear regulations and SOPs from the health office in maternal and child health service programs, human resources are very minimal and facilities and facilities are not feasible at supporting health centers in remote villages so that the service program provided is less than optimal. Conclusions: During the pandemic, some health facilities were closed and there were no services for MCH for a while. For services, it is directed to the designated health facility as a reference if there are complaints and are of an emergency nature. So there needs to be a policy for the sustainability of maternal and child health services during the pandemic.